Water Productivity of Mustard [Brassica juncea (L.)] in Relation to Deep Tillage and Irrigation Regimes - Madhu Dhingra; M.S. Kahlon; Jeevanjot Dhaliwal (Journal of the Indian Society of Soil Science, 2025)
Mustard (Brassica juncea) being a low water requiring crop provides a good alternative for crop diversification in the over-exploited region of north-west India. A two year field experiment was conducted in split plot design with three irrigation regimes in main plot viz. no post sowing irrigation (I0), one irrigation (I1) at 4 weeks after sowing (WAS) and two irrigations (I2)- one at 4 WAS and second in start of January and two tillage practices in sub-plot – conventional and deep tillage. The I2 irrigation regime resulted in higher relative leaf water content (85.65 at 105 DAS), SPAD value (45.88 at 105 DAS), number of siliquae plant-1 (409.30), seed (12.05 q ha-1) and stover yield (42.04 q ha-1). However, the seed yield was statistically similar (p≤0.05) under I1 and I2 irrigation regime during second year. Reduced mechanical resistance and higher periodic soil moisture content was observed in deep tilled plots. Deep tillage resulted in gain of seed yield (1.12 q ha-1) and stover yield (3.11 q ha-1) compared to conventional tillage. Water productivity was highest in plots with deep tillage and I1 irrigation regime. Seed yield of Brassica juncea with deep tillage and I1 was equivalent to conventional tillage with I2 thus suggesting saving of irrigation water (7.5 cm) with deep tillage. Therefore, study findings demonstrated that deep tillage with supplemental irrigation can be potential option for improving yield and water productivity of mustard.